Konstruktywistyczna dydaktyka w edukacji matematycznej - Alina Kalinowska-Iżykowska (Problemy Wczesnej Edukacji)
Didactics as science is a sub-discipline of paradigmatically pluralistic pedagogy. Its key categories, concepts, and relations between them are subject to changes in meaning. Constructivist mathematical education has to offer tools for a different understanding of educational phenomena. The text shows examples of significant transformations of didactic knowledge. The necessity to reconstruct how mathematical knowledge functions concerning students and teachers also implies requirement for changes in methodological assumptions. It becomes necessary to undertake qualitative research approaches to deepen the understanding of what is happening in lessons.